Innovation of Augmented Reality Learning Media Using Assemblr Edu to Improve Science Learning Motivation and Outcomes of Sixth Grade Students - Krismapera; Putrayasa, Ida Bagus; Sanjaya, Dewa Bagus (Papanda Publisher, 2025)
The development of digital technology necessitates innovation in learning media, particularly to enhance students’ motivation and learning outcomes in science education. One proposed solution is the use of augmented reality (AR)-based learning media through the Assemblr Edu platform. This study aims to develop and evaluate the feasibility of Assemblr Edu as a learning medium to improve the motivation and science learning outcomes of 30 sixth-grade students at SDN 218/IV Kota Jambi. This research is a development study (R&D) utilizing the ADDIE model, which includes five stages: Analyze, Design, Develop, Implement, and Evaluate. Data collection techniques included observation, interviews, questionnaires, and learning outcome tests. The validation results indicated that the media was highly feasible, with validation scores of 95% from material experts and 93.89% from media experts. The practicality test yielded scores of 96% from teachers and 97% from students. The effectiveness test results showed a significant improvement in students’ motivation and learning outcomes (Sig. 0.000 < 0.05). Therefore, the Assemblr Edu learning media is proven to be feasible, practical, and effective for use in science instruction to enhance students’ motivation and learning outcomes.